Endothelial Alpha-Parvin Controls Integrity of Developing Vasculature and Is Required for Maintenance of Cell–Cell Junctions. Issue 1 (19th June 2015) - Fraccaroli, Alessia; Pitter, Bettina; Taha, Abdallah Abu; Seebach, Jochen; Huveneers, Stephan; Kirsch, Julian; Casaroli-Marano, Ricardo P.; Zahler, Stefan; Pohl, Ulrich; Gerhardt, Holger; Schnittler, Hans-J.; Montanez, Eloi
Abstract : Rationale: : Angiogenesis and vessel integrity depend on the adhesion of endothelial cells (ECs) to the extracellular matrix and to adjacent ECs. The focal adhesion protein α-parvin (α-pv) is essential for vascular development. However, the role of α-pv in ECs in vivo is not known. Objective: : To determine the function of α-pv in ECs during vascular development in vivo and the underlying mechanisms. Methods and Results: : We deleted the α-pv gene specifically in ECs of mice to study its role in angiogenesis and vascular development. Here, we show that endothelial-specific deletion of α-pv in mice results in late embryonic lethality associated with hemorrhages and reduced vascular density. Postnatal-induced EC-specific deletion of α-pv leads to retinal hypovascularization because of reduced vessel sprouting and excessive vessel regression. In the absence of α-pv, blood vessels display impaired VE-cadherin junction morphology. In vitro, α-pv–deficient ECs show reduced stable adherens junctions, decreased monolayer formation, and impaired motility, associated with reduced formation of integrin-mediated cell–extracellular matrix adhesion structures and an altered actin cytoskeleton. Conclusions: : Endothelial α-pv is essential for vessel sprouting and for vessel stability. Abstract : Supplemental Digital Content is available in the text.